A Steady-State Monte Carlo Study on the Effect of Structural and Operating Parameters on Liquid Water Distribution within the Microporous Layers and the Catalyst Layers of PEM Fuel Cells. Issue 13 (2nd October 2018) - Pournemat, A.; Wilhelm, F.; Haußmann, J.; Vierrath, S.; Thiele, S.; Scholta, J.
Abstract : The distribution of liquid water agglomerations within a catalyst layer and a microporous layer of a polymer electrolyte membrane fuel cell employing a Monte Carlo model are simulated. The simulations are based on real material structures and locally resolved operating conditions. The 3D material structures are obtained from focused ion beam tomography capable of nm-scale imaging. The local temperature and the relative humidity profiles are provided by a computational fluid dynamics simulation, based on a single channel fuel cell model taking into account all relevant transport and electrochemical processes. The results of this Monte Carlo study confirm the strong dependency of the water saturation in the catalyst layer and microporous layer on the structural parameters and operating conditions, such as: wettability, pore size and local temperature and relative humidity.